UPAYA PEMERINTAH DAERAH DALAM MENINGKATKAN KESEJAHTERAAN PETANI KELAPA DI KABUPATEN INDRAGIRI HILIR, PROVINSI RIAU TAHUN 2016-2019 - Desti Milsi Anggraini; Zulfa Harirah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Indragiri Hilir Regency is an area that has palntations wide coconut area with 302.774 Area (Ha) and 317.117 tons of production coconut. So it is not suprising that almost 70% of the people Indragiri Hilir Regency make a living as coconut farmers. However, there is no guarantee the welfare of coconut farmers in Indragiri Hilir Regency because of the presence of problems that result in a decrease in the level of welfare coconut farmers in Indragiri Hilir Regency. Where is the rate drop the welfare of coconut farmers is caused by the problems that are found in the value chain of coconut production in Indragiri Hilir Regency. Therefore, this research was conducted to find out how the Local Government is improving the welfare of coconut farmers through the calue chain of coconut production in Indragiri Hilir Regency and what are the factors an obstacle to the efforts of the regional Government in improving the welfare of farmers coconut in Indragiri Hilir Regency. This research was conducted using a qualitative research approach with the type of descriptive research. With data collection techniques through interviews and documentation. The result of this study indicate that the government’s efforts in improving the welfare of coconut farmers through the production value chain coconut in Indragiri Hilir Regency include: 1) Government’s efforts as a regulator of the input-output structure which is carried out by establishing regulations relating to the problems of the input-output stucture that can be resulting in a decrease in the level of welfare of coconut farmers, 2) government efforts as Upgrading Facilitator, which is done by making dike and normalization of smallholder coconut plantation ditches, plantation rejuvenation community coconut, coconut production processing, and training of coconut farmers, 3) Government efforts as Facilitator of value chain breaking collectors (tauke) which is done by establishing and utilizing Bumdes in every village in Indragiri Hilir Regency, and 4) Government Efforts as a stakeholder dynamism carried out by conducting socialization, deliberation and cooperating with stakeholders to encourage the contribution of parties involved in a coconut production value chain to increase welfare of coconut farmers. While the inhibiting factors contained in local government efforts in improving the welfare of coconut farmers, namely : contained in the lack of budget, lack of human resources, and limited facilities and infrastucture. . Keywords : Local Government, Welfare, Coconut Farmers.